1995
DOI: 10.1247/csf.20.107
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Expression of the Cytoskeleton after Immortalization of Human Fibroblasts.

Abstract: ABSTRACT. Human diploid fibroblasts (HDF) have a limited in vitro lifespan of population doubling level (PDL) 50-70. The molecular mechanismunderlying cellular senescence and immortalization is not thoroughly understood. It has been reported that the cytoskeleton has diverse functions and may have a role in growth regulation through association with other cellular components.To shed light on the relationship between functions of the cytoskeleton and senescence or immortalization, we investigated the alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
2
7
0
1
Order By: Relevance
“…Thus, the senescent fibroblasts could express a high level of vimentin protein. In fact, the increased vimentin-expression in senescent cells observed in the present study is consistent with that reported with SV40-transformed, but senescent, human fibroblasts (SV40-transformed immortal counterparts on the contrary exhibit a reduced expression of vimentin) (Satoh et al 1994;Kaneko et al 1995). Similarly, an increase in vimentin has been reported with Sertoli cells in testis tubules of elderly men (de Miguel et al 1997) and with old rats' astrocytes, which contain bundles of hypertrophic intermediate filaments (Berciano et al 1995).…”
Section: Figsupporting
confidence: 93%
“…Thus, the senescent fibroblasts could express a high level of vimentin protein. In fact, the increased vimentin-expression in senescent cells observed in the present study is consistent with that reported with SV40-transformed, but senescent, human fibroblasts (SV40-transformed immortal counterparts on the contrary exhibit a reduced expression of vimentin) (Satoh et al 1994;Kaneko et al 1995). Similarly, an increase in vimentin has been reported with Sertoli cells in testis tubules of elderly men (de Miguel et al 1997) and with old rats' astrocytes, which contain bundles of hypertrophic intermediate filaments (Berciano et al 1995).…”
Section: Figsupporting
confidence: 93%
“…Loss of cytoskeletal architecture is thought to be a contributing factor, rather than a consequence, of neoplastic transformation (Janmey and Chaponnier, 1995;BenZe'ev, 1997;Pawlak and Helfman, 2001). Expression of several actin-binding proteins, including tropomyosin, vinculin, ␣-actinin, and gelsolin has shown to be downregulated in many transformed cells (Kaneko et al, 1995). Restoring these proteins can reverse the malignant phenotype in several different experimental models of transformation (Gluck et al, 1993;Braverman et al, 1996;Kwon et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting evidence for the involvement of cytoskeletal genes in senescence comes from several laboratories that have shown an increase in expression of cytoskeletal genes, such as vimentin and fibronectin, in senescent human fibroblasts (Murano et al ., 1991; Satoh et al ., 1994; Kaneko et al ., 1995). Among the genes that were overexpressed in senescent Werner syndrome fibroblasts, several are cytoskeletal related including fibronectin, PAI-1 and thrombospondin (Murano et al ., 1991; Lecka-Czernik et al ., 1996).…”
Section: Genomic Approaches To Identify Senescence/immortalization Gementioning
confidence: 99%